Utilisation of Extension Services for Climate Change Adaptation by Male and Female Arable Crop Farmers in Bayelsa State, Nigeria - Chinwoke Clara Ifeanyi-obi; Esther Tolumoyi (Journal of Agricultural Extension)
The research analysed differences in the use of extension services for climate change adaptation between male and female arable crop farmers in Bayelsa State, Nigeria. A hundred and sixty arable crop farmers were chosen for the study using a multistage sampling procedure. A questionnaire was used to gather data, while mean score, percentage, and t-test were used to analyse it. Results revealed moderate awareness of extension services across both genders, with female farmers reporting higher awareness in areas like flood prediction (89.7%) and weather forecasting (74.7%). However, male farmers had significantly greater access than females (t= 5.3) Similarly, the frequency of utilisation was significantly higher among males than females. While awareness is growing, both access to and utilisation of extension services remain gender-skewed and infrequent, limiting farmers' adaptive capacity. Gender-inclusive extension strategies, improved service consistency, targeted awareness campaigns implemented by trained extension agents, and provide targeted support to enhance women's access to and utilisation of climate-relevant agricultural services